Volume 4: Materials Technology 2015
DOI: 10.1115/omae2015-42184
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Stress Corrosion Cracking Susceptibility of the API 5L X70 Steel in Corn and Sugar Cane Ethanol Environments

Abstract: The interest in renewable and cleaner fuels has stimulated ethanol production in the last decades. Some of the drivers for that ever increasing production were the Brazilian Alcohol Program, Kyoto Protocol and the replacement in USA of the octane booster MBTE (methyl-tert-buthyl ether) for ethanol. The world’s largest producers of ethanol are The United States of America and Brazil, where the main sources are corn and sugar cane, respectively. Production flow via pipeline is the safest and most cost effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…However, in the present study, the X-70 steel did not show evidence that indicates the presence of SCC under the employed conditions. These results are consistent with those reported by Breitenbach et al, which suggests that the SCC phenomenon is attributed to the type of ethanol (cane) used in the gasohol blend [4,6]. The lack of susceptibility to SCC can result from the fact that the rate of passivation of the steel in both types of gasohol is too high.…”
Section: Ssrt Testsupporting
confidence: 92%
See 3 more Smart Citations
“…However, in the present study, the X-70 steel did not show evidence that indicates the presence of SCC under the employed conditions. These results are consistent with those reported by Breitenbach et al, which suggests that the SCC phenomenon is attributed to the type of ethanol (cane) used in the gasohol blend [4,6]. The lack of susceptibility to SCC can result from the fact that the rate of passivation of the steel in both types of gasohol is too high.…”
Section: Ssrt Testsupporting
confidence: 92%
“…The results showed behaviours that are consistent with those obtained by Rangel et al [38], who studied the susceptibility to SCC of an API X-80 steel using ethanol as a corrosive medium, concluding that the steel is susceptible to SCC only when FGE has 5% water + 10 mg/L sodium chloride. On the other hand, Breitenbach et al evaluated the susceptibility of an API 5L-X-70 steel to SCC in corn and sugarcane ethanol [6]. They observed that the corn ethanol medium generated SCC, while sugarcane ethanol did not.…”
Section: Ssrt Testmentioning
confidence: 99%
See 2 more Smart Citations
“…There are studies that have demonstrated the presence of the SCC phenomenon in certain microalloyed steel compositions in different bio-ethanol media, which is attributed the susceptibility of the material to the source of bio-ethanol; corn bio-ethanol is considered a factor that increases susceptibility and cane bio-ethanol shows immunity to SCC [32]. Many authors agree that two of the main factors in crack initiation caused by SCC are water and Cl- [14,15].…”
Section: Discussionmentioning
confidence: 99%